Diverse roles for the ror‐family receptor tyrosine kinases in neurons and glial cells during development and repair of the nervous system. Issue 1 (1st June 2017) - Endo, Mitsuharu; Minami, Yasuhiro
Abstract : The Ror‐family of receptor tyrosine kinases (RTKs) are involved critically in tissue genesis and organogenesis during development. In mammals, Ror1 and Ror2, members of the Ror‐family RTKs, have been shown to mediate cell polarity, migration, proliferation, and differentiation through the activation of noncanonical Wnt signaling by acting as receptors or co‐receptors for Wnt5a. Nematodes bearing mutations within the cam‐1 gene, encoding a Ror2 ortholog, exhibit defects in various developmental processes of the nervous system, including neuronal cell migration, polarization, axonal extension, and synaptic transmission. In mice, Ror2 and/or Ror1 are also shown to play roles in regulating neurite extension, synapse formation, and synaptic transmission of hippocampal neurons, indicating that the Ror‐family RTKs have evolutionarily conserved functions at least in part in neurons during development. Furthermore, Ror2 and/or Ror1 are expressed in neural stem/progenitor cells of the developing brain and in astrocytes of the adult brain after injury, and they play important roles in regulating cell proliferation under these different contexts. In this article, we overview recent advances in our understanding of the roles of the Ror‐family RTKs in the development and repair of the nervous system and discuss their potential for therapeutic targets to neurodegenerative diseases. Developmental Dynamics 247:24–32, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: In this review, we summarized current knowledge about the roles of the Ror‐family receptor tyrosine kinases in the development and repair of the nervous system after injury, and their possible implications in neurodegenerative diseases. In mammals, Ror2 as well as Ror1 acts as receptor for Wnt5a to mediate non‐canonical Wnt signaling, and it plays critical roles in regulating tissue‐ and organo‐genesis during development. Ror2 and/or Ror1 play roles in regulating cell proliferation of neural stem/progenitor cells in the developing brain and in astrocytes in the adult brain after injury.